The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/stc.2524
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement of base isolation systems by incorporating eddy current damping and magnetic spring under earthquakes

Abstract: Summary An innovative subsystem with the incorporation of eddy current (EC) damping and magnetic negative stiffness spring (MNSS) is proposed to develop feasible strategies for performance improvement of existing base isolation techniques. The concept of integrating the eddy current damping mechanism and the nonlinear negative stiffness spring is firstly introduced for better energy transition behavior under earthquake excitations. The analytical expressions of the force characteristics of the EC and the MNSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…5456 Case1 represents that stiffness K is the top priority, linearity L i is the second, and volumetric force G is less important than them, which is suitable for the applications with large stiffness or strong nonlinearity, such as vibration energy harvesters 13,14,49 and nonlinear vibration isolator. 9 The priority from high to low of Case 2 are linearity L i , stiffness K , and volumetric force G , which is suitable for linear machines. 6,7 The priority from high to low of Case 3 are volume force G , linearity L i , and stiffness K , which is suitable for aerospace field.…”
Section: Multi-objectives Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…5456 Case1 represents that stiffness K is the top priority, linearity L i is the second, and volumetric force G is less important than them, which is suitable for the applications with large stiffness or strong nonlinearity, such as vibration energy harvesters 13,14,49 and nonlinear vibration isolator. 9 The priority from high to low of Case 2 are linearity L i , stiffness K , and volumetric force G , which is suitable for linear machines. 6,7 The priority from high to low of Case 3 are volume force G , linearity L i , and stiffness K , which is suitable for aerospace field.…”
Section: Multi-objectives Optimizationmentioning
confidence: 99%
“…4 These characteristics are of great significance in improving vibration and noise, reducing energy consumption, and increasing service life and durability. 5 Therefore, PMS are widely used for motors, 6,7 robots, 8 vibration isolators, 9 static load compensation, 10 pumps, 11 valves, 12 energy harvesting, 13,14 and many other apparatuses.…”
Section: Introductionmentioning
confidence: 99%
“…Base isolated system could effectively protect buildings under high intensity ground motion (Losanno et al, 2021), and reduce the seismic response of structure (Cancellara and Angelis, 2016). Researchers have studied many kinds of isolated bearings and found that most of them can not only reduce the seismic response of the structure, but also control the displacement of the isolated story (Castaldo and Tubaldi, 2018; Fu et al, 2019; Shan et al, 2020; Shang and Hu, 2020). For the application of base isolated, Japan has more experiences than other countries (Pan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, multi-support excitation for long-span structures is used to ensure that the calculation results are similar to the actual seismic response. The Meilan Airport Phase II Project is the largest staggered isolated building in China, as shown in Figure 1 [1][2][3][4][5][6]. During an earthquake, the energy released by the earthquake is transmitted to the Earth's surface, causing the ground to vibrate.…”
Section: Introductionmentioning
confidence: 99%